КОГНИТИВНОЕ РАЗВИТИЕ ДОШКОЛЬНИКА - Тлеумбетова, К.Д. (SCIENCE and SOCIETY, 2018)
The article reveals the peculiarities of mental evolution of a preschool age child. At this age all mental life of a child and his attitude to the world is reconstructing. There were given the points view of scientists about peculiarities of mental evolution process of a child and the process of personal formation of a child.